Research Tests of Drill Seeder with Control and Monitoring Unit of Seed Metering Device for Differentiated Dosing of Seeds and Mineral Fertilisers in Precision Agriculture - Zolotukhin Yevgeniy; Nukeshev Sayakhat; Amantayev Maxat; Rustembayev Arman; Kakabayev Nurbol; Kravchenko Ruslan (Acta Technologica Agriculturae)
Precision agriculture based on differentiated dosing of seeds and mineral fertilisers allows for enhancing soil fertility while simultaneously increasing crop yields and reducing production costs. The purpose of study is to increase the efficiency of differentiated dosing of seeds and mineral fertilisers. By determining the intra-field variability of nutrient elements, it has been revealed that the content of mobile nitrogen (N), phosphorus (P2O5), and carbon (CO2) in the arable layer varies widely within one field. Based on the data obtained, the maps of the distribution of nutrients were constructed. The research tests of the drill seeder with the control and monitoring unit of seed metering device were conducted in this field conditions, and the results were processed using the method of variational statistics. The analysis of the assessment of agrotechnical performance of the seeder shows that the values of the unevenness of sowing between devices and the instability of total sowing (in the coefficients of variations, %) meet agrotechnical requirements. It was revealed that the seeder allows for smooth adjustment, reduces time, and increases the range of seeding rate and dosing of seeding material. The obtained data confirm the effectiveness of the seeder for differentiated dosing of seeding material in precision agriculture.